Redefining mathematics learning evaluation: From traditional assessment to technology-based holistic competency assessment - Nurwahid, Mohammad; Ashar, Sofia (LINEAR: Journal of Mathematics Education, 2025)
The development of digital technology encourages the redefinition of evaluation systems in mathematics learning to make them more relevant to the demands of the current curriculum. This study aims to identify digital and holistic assessment forms that can comprehensively measure students’ competencies, including cognitive, affective, and psychomotor aspects. The research method employed was a literature study using a Literature Review approach. The research instrument was a data extraction sheet used to record and analyze findings from selected publications. Data were collected from various databases and reputable journals published between 2014 and 2025. Out of 243 articles identified in the initial stage, 29 met the inclusion criteria and were analyzed further. The findings show that digital assessments through platforms such as Quizizz, Wordwall, and Google Form enhance interactivity, adaptivity, and student engagement. Meanwhile, project-based, portfolio, and observational assessments are proven to provide a more comprehensive picture of student learning outcomes. This study emphasizes the need for a shift from traditional evaluation to technology-based holistic evaluation in line with the demands of the 21st-century curriculum.